gη - Separation Axioms In Topological Spaces - et. al., K. Sumathi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper a new class of separation axioms in topological spaces is used in gη-closed sets. The concept of gη-Tk spaces for k = 0, 1, 2, gη-Dk spaces for k = 0, 1, 2 and gη-Rk spaces for k = 0, 1 and some of their properties are investigated.